Microstructural and ageing response assessment of eutectic Al-Cu alloy due to isothermal heat treatment in semisolid state. (6th January 2020) - Chaudhari, Abhimanyu; Nasker, Purnendu; Srivastava, Ankur; Paul, Sudeep; Chakrabarti, Ajit Kumar
Abstract: An as cast Al-33%Cu eutectic alloy has been processed by semisolid heat treatment, with the ultimate objective of developing a ductile and strong eutectic composite material for probable application as bearing materials and other sliding wear components. In this phase of work only microstructural characterises has been attempted. The as cast sample of Al–Cu alloy is subjected to isothermal heat treatment at a temperature of 560 °C for varying periods of time and followed by water quenched. The microstructures of the semisolid heat treated (SSH) samples are analysed using an optical microscope and scanning electron microscopy (SEM). The microstructures of the quenched Al-33%Cu alloy samples show lamellar to lamellar + dendritic transition after SSH treatment. The quenched microstructure after 20 min of holding time primarily consists of copper aluminide dendrites + supersaturated α –Al grains. A massive copper-aluminide (>80%Cu) intermediate phase is observed after 3 to 6 min SSH. The sample configuration did not change after semisolid heat treatment and water quenching. This suggest that complete remelting and overburning did not occur during the semisolid heat treatment. The SSH sample shows maximum hardness, after 10 min holding time compared to solution treated (at 560 °C) and aged (at 150 °C) sample of a standard Al-4.5%Cu cast alloy. The Transmission electron microscopy (TEM) micrograph of the as quenched 10 min. SSH sample shows rod shaped CuAl2 ( θ ) precipitates, a dislocation network, cellular subgrains and an extremely fine lamellar eutectic. Solute cluster probably Guinier–Preston (GP) zones, precipitates and fine α –Al grains was observed in the peak aged sample. The x-ray diffraction (XRD) analysis of aged SSH treated sample shows several intermetallic copper-aluminide phases in each sample.